Resources and Results in Union Rivalry: A Case Study - Mount, Joan; Siegel, Jacob P. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
This paper shows the asymetric disequilibrium between available resources and results in the course of a union recruiting campaign in a case study of an experience of CUPE and LUSSA at Laurentian University.